Upaya Peningkatan Kualitas Pelayanan Untuk Meningkatkan Kepuasan Pelanggan Di Alinea Catering - Swastono Putro Pirastyo; Angga Alviana Putra; Yuliana Pinaringsih Kristiutami (Journal of Tourism and Economic, 2020)
The increasing growth of culinary service providers in Bandung has made competition in the culinary world even tighter. Service and product quality is the stake of every service provider to remain competitive in this industry. This study aims to find out, how are the form of service quality received by customers in the catering industry, the form of quality improvement efforts, and the form of handling customer complaints. This research was conducted in Alinea Catering, using qualitative descriptive methods. From the results of this study, it was found that basically the quality of services provided was still not good, with the determination of service standards that were deemed not optimal. This is because the standard setting has not been done in writing in a standard operating procedure. So this has an impact on the implementation of service quality and handling of complaints that cannot be measured with certainty. However, efforts to improve service quality have been well illustrated, by increasing employee education standards, increasing wages, and updating work uniforms regularly.